COMPARISON OF SEMEN QULAITY FOR THREE LINES OF HOLSTEIN BULLS: 1. SOME IMMEDIATE AND MICROSCOPIC CHARACTERISTICS - Al-Saedi, A. J. A.; Abdulkareem, T. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was conducted to compare the semen immediate and microscopic characteristics of the three lines of Holstein bulls. Twenty-one Holstein bulls were divided into three groups belonging to the three lines of Holstein bulls; born in Iraq (Australian origin; n = 8), resulting from embryo transfer technology (New Zealand origin; n = 7), as well as the first generation (F1) resulted from two parents obtained from embryo transfer technology in Iraq (New Zealand origin; n = 6). The ET and L groups showed greater (P≤0.01) ejaculate volume, live sperms percentage, and plasma membrane integrity percentage compared to the F1 group of bulls. Moreover, ET bulls exhibited higher (P≤0.01) sperm concentration than L and F1 bulls. The ET and F1 bulls were superior (P≤0.01) to L bulls in the percentages of sperm’s cell individual motility and normal sperms. The percentage of DNA damage was significantly (P≤0.05) decreased in the F1 group compared to the L group but did not differ from those of the ET group. In conclusion, the ET and F1 Holstein bulls were superior to L bulls in most immediate and microscopic semen characteristics and their adaptation to the Iraqi environment.